1998
DOI: 10.1046/j.1365-201x.1998.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere infusion reverses vasoconstrictor‐mediated change in hindlimb oxygen uptake and energy status

Abstract: The vasoconstrictors, angiotensin II (AII) and serotonin (5-HT) produce opposing metabolic effects and appear to control different flow routes in the constant-flow perfused rat hindlimb. In the present study the association between vascular flow route recruitment and metabolism was assessed by selective microsphere embolism of either route. Microspheres (MS, 11.9 +/- 0.1 microns, mean +/- SE diameter) were injected during AII, 5-HT or vehicle infusions (basal conditions) and the effects on hindlimb (4.7 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…It is important to note that there are similarities in the effect on muscle metabolism after introduction of the MS (particularly 30 × 10 6 MS) to what has been observed previously when 5-HT was infused [31]. In both situations, when the muscle has been freeze-clamped and assayed, the EC remained unaffected, but the PCr/Cr ratio was decreased by approx.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It is important to note that there are similarities in the effect on muscle metabolism after introduction of the MS (particularly 30 × 10 6 MS) to what has been observed previously when 5-HT was infused [31]. In both situations, when the muscle has been freeze-clamped and assayed, the EC remained unaffected, but the PCr/Cr ratio was decreased by approx.…”
Section: Discussionsupporting
confidence: 57%
“…Thus the inhibitory effect of 5-HT on hindlimb muscle metabolism was partly reversed by injection of MS [31], even though the perfusion pressure increased further. Thus we concluded that, if 5-HT had acted to vasoconstrict entry to the nutritive route and redirect flow to the non-nutritive route, the addition of MS lodged in the non-nutritive route redirected flow back to the nutritive route and, hence, the partial recovery of metabolism.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As indicated above, the constant vasomotion activity may allow the sharing of this over the entire muscle with time. Evidence to date shows that only the phosphocreatine-to-creatine ratio is compromised by a low ratio of nutritive to nonnutritive flow, and this is reversed when the nutritive-to-nonnutritive ratio is increased (187). For present considerations, the presence of this nonnutritive route in muscle may explain two phenomena that are developed further in sections below.…”
mentioning
confidence: 79%
“…This is believed to be partly the result of an altered perfusion pattern, through an increase in arteriovenous shunting away from the affected capillary bed. 20 , 21 Also, it can be speculated that the oxygen extraction capacity of the tissue is reduced as a result of its congested state and that the metabolic activity of the congested tissue is downregulated by the increased release of vasoactive substances, including adenosine, 22 and serotonin 23 as well as a decreased release of nitric oxide. 24 Similar results have been reported in experimental models of vascular trauma, in which an uncoupling was suggested between tissue metabolism and altered microvascular blood flow.…”
Section: Discussionmentioning
confidence: 99%